2023
DOI: 10.21926/obm.icm.2301014
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Burnout and Well-Being in Higher Education Health Science Faculty

Abstract: This study aimed to examine and compare the extent of burnout among health science faculty at a higher education institution and their self-reported perception of well-being during the COVID-19 pandemic. The design of the study was cross-sectional, descriptive survey research. An electronic questionnaire was developed to measure the constructs of burnout and well-being. Validated instruments used in the survey included the Oldenburg Burnout Inventory (OLBI) and the World Health Organization-5 Well-being Index.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The overwhelming shift in responsibilities of these faculty to not only ensure that students could navigate the challenges relating to COVID-19 while meeting academic requirements but also navigate their own challenges with limited social connectivity seems to have had an impact on the perception of overall wellness. Although the quantitative results of this investigation identified that this sample perceived themselves as generally “well” (McHenry et al, 2023 ); there were several qualitative responses that indicated a subsample of faculty who were struggling. An assessment of the degree to which the greater population of higher education faculty has been affected by impacts related to the COVID-19 pandemic has been slow to emerge.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…The overwhelming shift in responsibilities of these faculty to not only ensure that students could navigate the challenges relating to COVID-19 while meeting academic requirements but also navigate their own challenges with limited social connectivity seems to have had an impact on the perception of overall wellness. Although the quantitative results of this investigation identified that this sample perceived themselves as generally “well” (McHenry et al, 2023 ); there were several qualitative responses that indicated a subsample of faculty who were struggling. An assessment of the degree to which the greater population of higher education faculty has been affected by impacts related to the COVID-19 pandemic has been slow to emerge.…”
Section: Discussionmentioning
confidence: 76%
“…Faculty with clinical teaching responsibilities reported higher rates of burnout. Complete findings of the quantitative portion of the study are reported elsewhere (McHenry et al, 2023 ). The predetermined themes were interwoven throughout the narrative responses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although these demands predate the COVID-19 pandemic (Kinman & Johnson, 2019;Watts & Robertson, 2011) it focussed attention on employee wellbeing (de los Reyes et al, 2022;Schwab et al, 2022;Shen & Slater, 2021). For many educators, the stress of the pandemic was exacerbated by the rapid shift to emergency remote education (McHenry et al, 2023;Schwab et al, 2022) while simultaneously managing health concerns and responding to pastoral concerns and the digital poverty experienced by many students (Hardman et al, 2022;Husbands & Prescott, 2023) alongside experiences of loneliness, isolation, digital fatigue and high levels of anxiety (Hurria, 2023). These cumulative demands on educators demonstrated the complex and dynamic environment educators work within and the potential threats to wellbeing as well as their resilience .…”
Section: Advancing a Systems Approach To Educator Wellbeingmentioning
confidence: 99%